Challenges of Amnesty Programme for Post Conflict Peacebuilding in Nigeria’s Niger Delta - Agbegbedia, Anthony; Fadope, Matthew (ARRUS Journal of Social Sciences and Humanities, 2025)
This study examined the mechanism for post conflict peacebuilding of the amnesty programme in the Niger Delta, with emphasis on the challenges faced in attaining sustainable peace and development in Ondo state of the region. Both primary and secondary means of data collection were adopted for the study. The primary source included the use of key informant interview while the secondary data included published text books, journals and online materials. Atlas Ti was used to analyze data collected for more qualitative insight into the findings. Findings revealed that the approach is not effective, because militants were disarmed without proper mobilization and empowerment process. Other challenges faced by the amnesty programme which are so fundamental to post conflict peacebuilding ranged from inability of the government to properly mobilized and empowered ex-combatants after acquiring the basic education or skills, corruption, political influence to lack of proper monitoring. More so, the program did not include all those involved in the Niger Delta struggle and it was perceived by residents of the region as having some political undertone. In sum, the program is yet to achieve post conflict peace building in Ondo state of the region as expected.